For Professional Educators, What Is ‘Meaningful Collaboration’? - Blokhuis, JC (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
The Author argues that professionals can collaborate meaningfully only with persons committed to achieving the same ends. For educators, a professional commitment to helping students lead flourishing adult lives precludes collaboration with persons whose primary interests are pecuniary. Keywords: collaboration; educational goals; public education policy; higher education; human flourishing; entrepreneurs Résumé L’auteur soutient que les professionnels, en général, ne peuvent collaborer de façon significative, seulement qu’avec des personnes engagées à atteindre les mêmes buts. Pour les enseignants, un engagement professionnel dédié à aider leurs élèves à développer une vie d’adulte épanouie se trouve en opposition lorsqu’il vient à collaborer avec des personnes dont les intérêts primaires sont pécuniaires, comme les professionnels de l’éducation. Mots clés: collaboration; buts de la formation; politique d’enseignement publique; éducation supérieure; épanouissement humain; entrepreneurs